2020
DOI: 10.1051/e3sconf/202019503004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coal on mine tailings’ water permeability and water retention

Abstract: For safe and efficient mining operations to occur the management of waste materials is required, which often takes the form of geotechnical structures constructed from this waste. The safe use of these structures requires a number of resources, one of these being sufficient information about the waste material properties. For example, the drying process of a tailings dam is predicted with the water retention and permeability of the tailings. When considering coal tailings, which are comprised of coal and miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Indeed, coal macerals are known to be more hydrophobic than minerals [37][38][39][40][41][42] and the contact angle of a given fraction depends on the relative proportion of macerals and minerals. In addition, it was found that those proportions vary with particle size [46].…”
Section: Pore Size Distribution To Water Retention Curvementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, coal macerals are known to be more hydrophobic than minerals [37][38][39][40][41][42] and the contact angle of a given fraction depends on the relative proportion of macerals and minerals. In addition, it was found that those proportions vary with particle size [46].…”
Section: Pore Size Distribution To Water Retention Curvementioning
confidence: 99%
“…Thus, consideration of the contact angle of a material is relatively simple to implement, at least for materials that have the same contact angle for every particle. However, coal tailings contain a mixture of coal and mineral particles, and the coal particles can be more prevalent for particular size ranges, as indicated by the correlation between specific gravity (G s ) and particle size for one studied coal tailings [46]. No models have been found that can consider contact angle variations with particle size; however, for GSD-WRC models in particular, it would be simple to implement such the correction in [37], as a suction is associated with each particle size range.…”
Section: Contact Angle Between Water and Soil Surfacementioning
confidence: 99%
“…Moreover, except those wastes buried permanently below the water table, most CMWGs are unsaturated, yet there are few experimental researches in the literature characterizing the unsaturated properties of CMWGs. The most recent studies (Fityus and Li 2006;Vidler et al 2020) highlighted the importance of mineralogical composition, grain size distribution (GSD), pore size distribution (PSD), weathering and fabric, water retention and permeability.…”
Section: Sasan Power Ltd and Ors 2020)mentioning
confidence: 99%
“…Ding and Liu (2021) immersed a soft slate in water for different durations and found that it disintegrates into particles with GSDs obeying different fractal distributions. Latest studies show that the GSDs of many mine tailings (Qiu and Sego 2001;Vo et al 2020) and coal tailings (Islam 2021;Salam et al 2019;Vidler et al 2020) also exhibit fractal characteristics. Russell (2010) described a GSD exhibiting a single fractal scaling as:…”
Section: Influence Of Clay Minerals On the Plasticity Of Cmwgs And Co...mentioning
confidence: 99%
See 1 more Smart Citation